2023
DOI: 10.3390/app13052882
|View full text |Cite
|
Sign up to set email alerts
|

Nature-Based Solutions for Flood Mitigation and Soil Conservation in a Steep-Slope Olive-Orchard Catchment (Arquillos, SE Spain)

Abstract: The frequency and magnitude of flash floods in the olive orchards of southern Spain have increased because of climate change and unsustainable olive-growing techniques. Affected surfaces occupy >85% of the rural regions of the Upper Guadalquivir Basin. Dangerous geomorphic processes record the increase of runoff, soil loss and streamflow through time. We report on ripple/dune growth over a plane bed on overland flows, deep incision of ephemeral gullies in olive groves and rock-bed erosion in streams, showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…In this context, we recently showed that highly resolved computational fluid dynamics simulations of hydrological and hydraulic processes, using the 2D Saint-Venant equations, yield the optimal location of NbS (e.g., natural and artificial wetlands, vegetal cover, riparian restoration, gravels seeding in streambeds, etc.) to provide the most benefits for minimising the water discharges and the erosion-prone area, maximising the soil infiltration capacity [46]. Consequently, the location and restoration of extinct wetlands, or even the artificial creation of new ones, are of great importance for adaptation to climate change since they reduce the risk of flooding and minimise the effects of drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we recently showed that highly resolved computational fluid dynamics simulations of hydrological and hydraulic processes, using the 2D Saint-Venant equations, yield the optimal location of NbS (e.g., natural and artificial wetlands, vegetal cover, riparian restoration, gravels seeding in streambeds, etc.) to provide the most benefits for minimising the water discharges and the erosion-prone area, maximising the soil infiltration capacity [46]. Consequently, the location and restoration of extinct wetlands, or even the artificial creation of new ones, are of great importance for adaptation to climate change since they reduce the risk of flooding and minimise the effects of drought.…”
Section: Discussionmentioning
confidence: 99%
“…In the current context of adaptation to climate change, this technique can be a handy, inexpensive, and agile resource for managers to conserve this type of ecosystem and their biodiversity. Furthermore, the recovery and restoration of wetlands could mitigate other types of threats related to extreme climate events by reducing the risk of flooding, especially in towns surrounded by agricultural areas with null soil protection, and favours the recharge of aquifers [46].…”
Section: Discussionmentioning
confidence: 99%